The Innovation of Digital Payment System with QRIS in National Open API and Maqasid al-Sharia Standards - Sarif, Akbar; Ariyanti, Rini (AIBPM Publisher, 2024)
QRIS is a digital payment system innovation standardized as a national QR code in Indonesia. This paper analyzes the National Open API and Maqasid al-Sharia standards within the QRIS digital payment system. Employing a qualitative descriptive methodology, the study determined that Bank Indonesia formulated three National Open API standards: governance guidelines, data standards with technical specifications, and technical and safety standards. Aligned with Maqasid al-Sharia, the analysis reveals a significant correlation between QRIS and its core tenets, specifically Hifz ad-Din (safeguarding religion) and Hifz al-Mal (preserving wealth). Moreover, viewing maqasid as a methodological framework, QRIS is deemed a legal and halal system conforming to maqasid. This topic can be examined from five dimensions: the payment system's alignment with Sharia law, its widespread use among traders (urf tujjar), the contractual adherence (ijab qabul) to Islamic sharia and user benefits, the reflection of service value in QRIS service fees, and mutual advantages for both parties. Regarding maslahah, QRIS falls under dzanni maslahah, necessitating its implementation to be entrusted to contemporary mujtahids for the continued benefit of users.